Document Quality Indicators and Corpus Editions - Crane, Gregory; Rydberg-Cox, Jeffrey A.; Mahoney, Anne (Tufts Archival Research Center, 2005)
Corpus editions can only be useful to scholars when users know what to expect of the texts. We argue for text quality indicators, both general and domain-specific.